Cardiovascular Response of Aged Outpatients With Systemic Diseases During Tooth Extraction: A Single-Center Retrospective Observational Study - Li, Jinjin; Tian, Zhiyan; Qi, Shuqun; Zhang, Jiankang; Li, Longjiang; Pan, Jian (Frontiers in Public Health, 2022)
Background: Aged people are maintaining many natural teeth due to the improved oral health. However, the compromised general health and poor oral hygiene habits at earlier ages resulted in a poor status of preserved teeth. Therefore, tooth extraction is required in many aged people. More knowledge is needed because there are many risk factors during the surgery in frail aged adults. The aim of this study was to evaluate the cardiovascular response of such a population during tooth extraction and analyze risk factors to provide clinical guidance. Methods: A retrospective study was performed on aged patients with systemic diseases who underwent tooth extraction. Data regarding demographic profiles and cardiovascular parameters of heart rate and blood pressure were collected preoperative, when local anesthesia was administered, at the beginning of tooth extraction, 5 minutes after tooth extraction and postoperative. The effects of risk factors, including age, sex, and systemic diseases on these parameters were analyzed with a multilevel model. Results: Heart rate (HR), systolic blood pressure (SBP) and diastolic blood pressure (DBP) of aged patients increased significantly when performing local anesthesia and tooth extraction. During the operation, the older patients (β = 2.011, P= 0.005) and the diabetics (β = 3.902, P < 0.0001) were associated with higher SBP, while those with more tooth extractions exhibited higher HR (β = 0.893, P = 0.007). Female patients showed both significantly elevated HR (β = 1.687, P < 0.0001) and SBP (β = 2.268, P < 0.0001). However, for coronary artery disease patients, HR (β = -2.747, P < 0.0001) and blood pressure (SBP (β = -4.094, P < 0.0001) and DBP (β = -0.870, P = 0.016)) were markedly lower than those of patients without a diagnosis of coronary artery disease. Conclusion: Cardiovascular response of aged outpatients with systemic diseases during tooth extraction is quite significant. Age, sex, systemic diseases and the number of tooth extraction could be risk factors closely associated with cardiovascular response. The findings might provide the safety guidance for dentists on tooth extraction in this population. Keywords: tooth extraction, aged patients, systemic diseases, heart rate, blood pressure, multilevel model